Hydrogen bonding phase-transfer catalysis with ionic reactants: enantioselective synthesis of γ-fluoroamines - Roagna, G; Ascough, DMH; Ibba, F; Vicini, AC; Fontana, A; Christensen, KE; Peschiulli, A; Oehlrich, D; Misale, A; Trabanco, AA; Paton, RS; Pupo, G; et al. (American Chemical Society, 2020)
Ammonium salts are used as phase-transfer catalysts for fluorination with alkali metal fluoride. We now demonstrate that these organic salts, specifically azetidinium triflates, are suitable substrates for enantioselective ring opening with CsF and a chiral bis-urea catalyst. This process that highlights the ability of hydrogen bonding phase-transfer catalysts to couple two ionic reactants, affords enantioenriched γ-fluoroamines in high yields. Mechanistic studies underline the role of the catalyst for phase-transfer, and computed transition state structures account for the enantioconvergence observed for mixtures of achiral azetidinium diastereomers. The N-substituents in the electrophile influence reactivity, but the configuration at nitrogen is unimportant for enantioselectivity.